Towards inclusive and egalitarian vocational education and training : key challenges and strategies from a holistic and multi-contextual approach : proceedings of the 6th Crossing Boundaries Conference in Vocational Education and Training, Palma, Mallorca, Spain, 21 to 23 May 2025 - Quintana-Murci, Elena [Herausgeber]; Salvà-Mut, Francesca [Herausgeber]; Stalder, Barbara E. [Herausgeber]; Nägele, Christof [Herausgeber] (My University, 2025)
"This volume features 70 contributions that reflect the diverse and evolving field of VET research in 2025. Centred on the theme 'Towards Inclusive and Egalitarian Vocational Education and Training: Key Challenges and Strategies from a Holistic and Multi-Contextual Approach', the papers tackle critical issues related to access, participation, educational outcomes, and reforms in VET across various regions and contexts. A key issue highlighted in many papers is the impact of structural inequalities on participation in various VET pathways and their associated career prospects. Several studies indicate persistent trends of gender segregation, socio-economic divides, and challenges faced by migrants. Additionally, some studies explore how vocational aspirations develop and are limited across different educational systems and emphasise that targeted support, along with acknowledgement of learners’ backgrounds and goals, can enhance participation and outcomes. Another key focus is on transitions and trajectories – not just from school to work, but throughout the life course. Whether examining early vocational decision-making, adult learning, or mid-career upskilling, many contributions emphasise the need for VET systems to accommodate diverse and non-linear educational journeys. The development of VET professionals represents a third major strand. Several papers argue that inclusive VET needs a redefinition of the roles and skills of teachers, trainers, and guidance personnel." (Editors, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 1.3.2.2 Übergänge; P 3.2 Lehrpersonal; 370; Berufsbildungsforschung; Bildungschancengleichheit; Inklusion; Arbeitsmarktintegration; Geschlechtersegregation; Berufseinmündung; Bildungspersonal